Transformation Bedhaya Dance in Java Society: Rituals, Ceremonials, Entertainment - R.M. Pramutomo; Sriyadi Sriyadi (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: Bedhaya is a dance genre that lives and develops in Javanese society. This dance is a legacy of the times of the Hindu Buddha. In the course of the bedhaya dance era, it changed. This article aims to reveal the changes in the dance function of bedhaya and to examine its existence in Javanese society. The research used is qualitative with a historical approach. The data collection technique used is the archival studies method. The result showed bedhaya dance derived from the dance offerings performed by devadaҫi. In the times of Mataram Islam, it was used to legitimize the king’s position. The Bedhaya dance had a significant role in maintaining the king's authority when the palace lost political, economic, and juridical power during colonialism. During its development, the palace was only for cultural preservation. It can be presented outside the palace walls as an art of tourism. In the modern era, Bedhaya dance is one of the references in creating contemporary dance. The change in the function of the Bedhaya dance is accompanied by changes in how it is presented, the accompanying narrative, and the essence conveyed. This shows that changes in the views and ideas of Javanese society influence its artistic creations. Abstrak: Tari bedhaya adalah salah satu genre tari yang hidup dan berkembang di masyarakat Jawa. Tari ini merupakan sebuah warisan dari zaman Hindu-Budha sampai sekarang. Dalam perjalanannya dari masa-kemasa tari bedhaya mengalami perubahan. Penulisan artikel ini ingin mengungkapkan perubahan fungsi tari bedhaya, guna mengatahui eksistensinya dalam masyarakat Jawa. Bentuk penelitian yang digunakan adalah kualitatif dengan pendekatan sejarah. Teknik pengumpulan data menggunakan metode studi arsip. Hasil penelitian menunjukkan, tari bedhaya bersumber dari tari persembahan yang dilakukan oleh para devadaҫi. Pada zaman Mataram Islam tari bedhaya digunakan sebagai sarana legitimasi kedudukan raja. Tari bedhaya memiliki peranan signifikan dalam menjaga kewibawaan raja ketika kraton kehilangan kekuasaan politik, ekonomi, dan yuridis pada masa kolonialisme. Dalam perkembangannya, kraton hanya menjadi wadah pelestarian budaya. Tari bedhaya dapat disajikan di luar lingkungan kraton yang berfungsi sebagai seni pariwisata. Di era modern, tari bedhaya menjadi salah satu referensi dalam penciptaan karya tari kontemporer. Perubahan fungsi tari bedhaya disertai perubahan cara penyajian, narasi yang menyertai, serta esensi yang disampaikan. Hal ini menunjukkan bahwa perubahan pandangan dan gagasan masyarakat Jawa berpengaruh pada kreasi seninya.